An accelerated corrosion-fatigue testing methodology for offshore wind applications. (1st August 2021) - Mehmanparast, Ali; Vidament, Azenor
Highlights: A new methodology has been proposed for accelerating S-N fatigue and crack growth test in seawater. The proposed methodology uses high temperature fatigue data to predict lower temperature fatigue behaviour. The results show that generating S-N fatigue design curves in seawater can be accelerated by at least factor of two. The results show that the corrosion-fatigue crack growth tests can be accelerated by at least factor of three. The proposed methodology is mostly suitable for characterising the long-term fatigue behaviour of offshore structures. Abstract: Offshore wind turbines are subjected to cyclic loading conditions during their operational lifespan which is typically between 20 and 25 years. An important issue in fatigue design and integrity assessment of offshore wind turbine foundations is the examination of the long-term fatigue and corrosion-fatigue behaviour of steel structures in the high cycle region. High cycle fatigue tests, particularly at low frequencies in a seawater environment, are time-consuming and costly. Therefore, there is an essential need to perform accelerated tests to predict the long-term behaviour of the structures under realistic operational loading conditions. In this work, the existing fatigue acceleration mechanisms have been reviewed and a novel methodology has been proposed for accelerated testing and analysis of fatigue data in different environments (i.e. air, salt-spray and seawater) at higher temperatures. Two distinct equations have been developed and proposed for the calibration and prediction of S-N fatigue life and crack growth behaviour of steels in different environments. The proposed methodology has been validated through comparison with the existing data in the literature and predictions have been made at operational temperatures using high temperature data. The proposed approach is relatively simple to calibrate for a material of interest and enables accelerating S-N fatigue and crack growth testing of the examined materials by a factor of two and three, respectively. The proposed methodology and the obtained results have been discussed in terms of the need for accelerated testing for fatigue design and integrity assessment of offshore wind monopiles, especially those which are close to the end of initial design life and need a comprehensive engineering analysis for life extension or decommissioning.